Reproductive Dynamics of the Large Yellow Croaker Larimichthys crocea (Sciaenidae), A Commercially Important Fishery Species in China - Yan, Li-ting; Jiang, Yan; Xu, Qing; Ding, Guang-mao; Chen, Xin-yi; Liu, Min (Frontiers in Marine Science, 2022)
The large yellow croaker Larimichthys crocea (Richardson, 1846) (Sciaenidae) is distributed in southern Yellow Sea, East China Sea, and northern South China Sea of China and is a commercially important nearshore fishery species. L. crocea was listed on the IUCN Red List as “Critically Endangered” in 2020 mainly due to the over-exploration of its spawning and over-wintering aggregations in the 1950s–1980s throughout its distribution region. However, detailed studies on reproductive dynamics of L. crocea were limited in the past three decades. In this study, the reproductive dynamics of L. crocea was examined in the traditional Guanjingyang (GJY) spawning ground, one of the 15 well-known ones in its distribution region. Samples were collected using set nets from April 2019 to November 2021 to ensure at least 20 samples for all 12 months. A total of 1,006 individuals were caught, ranging from 46 to 391 mm standard length (SL) and 1.45 to 1,110.05 g body weight (BW). A growth dimorphism was found between sexes with females heavier than males when body sizes exceeded 61 mm SL (non-parametric ANCOVA, p < 0.01). Gonad histology of all 1,006 individuals revealed, for the first time, that L. crocea was able to spawn almost year-round for both females and males. Two spawning peaks, spring and autumn, were identified in March and May and in November for females and in April to June and in October to November for males. The minimum sizes at sexual maturity were 160 mm SL for females and 112 mm SL for male. The sizes at 50% sexual maturity were 187.2 mm SL for females and 150.2 mm SL for males. Results showed that the minimum SL for female maturity decreased about 20% in the past six decades. The spawning peaks were 2 months earlier in spring and 1 month extension in autumn in GJY. Clearly, the national fishing moratorium regulation in May to August, an important fishery management measure in China, can only protect the spring spawning peak partly. Further evaluation on the influence of climate change on reproductive strategies and stock recruitment of L. crocea is highly recommended.